Persepsi Mahasiswa Fakultas Pertanian Program Studi Agribisnis Terhadap Pekerjaan Dan Lapangan Pekerjaan Di Sektor Pertanian - Kalupa, Elsavera Yuliafni; Taroreh, Melissa Lady Gisela; Waney, Nordy Fritsgerald Lucky (AGRI-SOSIOEKONOMI, 2023)
This study aims to determine the perceptions of agricultural faculty students in the agribusiness study program on jobs and employment in the agricultural sector. This research was carried out for 3 months, from August to October 2022. The data used in this study are Primary Data and Secondary Data. Primary data was obtained from the distribution of research questionnaires that had been prepared and given directly to students of the agricultural faculty of the agribusiness study program. Secondary data was obtained from a list of the number of active students from the agricultural faculty of the agribusiness study program. In this study, the number of respondents was 100 students using the Purposive Sampling method, namely by taking respondent data from students of the agricultural faculty of the agribusiness study program who were active and in accordance with predetermined criteria. The method of data analysis was descriptive analysis using likert scale.